Preventive Effects of Resveratrol against Schistosoma mansoni-Induced Liver Fibrosis in Mice - Ismeil, Abderrhman AM; Soliman, Gehan Yassin; Sharara, Gihan M. (Gezira Journal of Health Sciences, 2016)
Abstract: Background : In Schistosomiasis, hepatocyte injury and Kupffer ’ s cell activation can result in reactive oxygen species generation, pro-inflammatory and profibrogenic mediators release. This can result in stellate cells activation and consequently, liver fibrosis. Resveratrol, a natural polyphenol, has been shown to possess antioxidant and anti-inflammatory properties. However, studies into its protective effects against Schistosoma mansoni -induced liver fibrosis are limited. Aims: The present study was designed to examine the preventive effects of resveratrol on Schistosoma mansoni -induced liver fibrosis in mice. Methods : Sixty male albino mice were divided into four groups of 15 mice as follows: normal resveratrol-untreated, normal resveratrol-treated, Schistosoma mansoni -infected resveratrol-untreated and schistosoma mansoni -infected resveratrol-treated. At the end of the experimental period, blood samples were collected to measure serum aspartate aminotransferase (AST), alanine aminotransferase (ALT), and TNFα. Liver tissue was collected for malondialdehyde (MDA) measurement and histopathological examination. Results : AST, ALT and TNF-α, and MDA levels were significantly increased in the infected resveratrol-untreated group compared to normal resveratrol-untreated group (all, P < 0.05). However, their levels were significantly decreased in the infected resveratrol-treated group compared to infected resveratrol-untreated group (all, P < 0.05).In addition resveratrol treatment improved S. mansoni -induced liver damage in IT group as it reduced the fibrosis compared to IU group. Conclusion : Results of the study indicate that resveratrol can prevent S. mansoni- induced liver fibrosis via mechanisms involving its anti-oxidant and anti-inflammatory anti-fibrotic properties.br>